Reduction in Path Failures by Adopting Multi-Channel Multi -Path in Routing For Dynamic Activity of Primary Users - Mishra, Priyank; Kumar Tiwari, Brajesh (International Journal of Engineering and Technology, 2018)
The Cognitive radio (CR) expertise has been recently proposed to deal with the spectrum shortage problem resulted by inappropriate spectrum supervision policies by enabling unauthorized users to use the authorized spectrum band in opportunistic and non-intrusive vigilant approach. In CRAHNs, the data routing is one of the main challenge as the channel accessibility and the activity of primary users are unpredictable. In this article, a new algorithm is proposed which counteracts the problem of path failure by adopting multi-channel multi-path reverse route for RREP packets. The protocol utilizes the hybrid of path and spectrum diversity techniques in routing. The performance assessment is conducted through simulation using the NS-2 simulator. The performance of the proposed protocol is compared with CAODV and D2CARP protocols in terms of packet delivery ratio, average energy, end-to-end delay, throughput, overhead and hop-count. The simulation consequences prove that the proposed protocol do better than CAODV and D2CARP in terms of the above mentioned performance metrics.Â